Aksi Jaga Pesisir : Penanaman Mangrove di Desa Sungai Bakau Kecil Kalimantan Barat - Safitri, Ikha; Sofiana, Mega Sari Juane; Hermawansyah, Hermawansyah; Ardiansyah, Lani; Reza, Mohammad (Indonesian Journal Publisher, 2024)
Mempawah Regency, located on the coast of West Kalimantan, has extensive mangrove potential, including in Sungai Bakau Kecil Village, with major species such as Avicennia, Rhizophora, Bruguiera, Sonneratia, and Nypa. Mangrove ecosystems, known to be among the most productive, have vital roles in social ecology, economy, and culture. However, most mangroves are degraded due to human activities. One approach to restoring degraded mangrove forests is through rehabilitation that involves local communities. This Community Service activity aims to maintain the sustainability of coastal ecosystems, while providing education on mangrove rehabilitation using traditional methods such as bamboo sleeves as one of local wisdom. The activity was carried out on 24-26 May 2024 in the mangrove area of Desa Sungai Bakau Kecil, involving lecturers and students of Marine Science Department, Gemawan Institute, and the local community. Mempawah Regency is experiencing coastline changes due to abrasion and accretion, causing damage to mangrove ecosystems in this region. Mangrove planting activities in Desa Sungai Bakau Kecil using local mangrove Rhizophora sp. with the bamboo sleeve method showed a high growth percentage (80-90%). In addition, the participants' level of understanding of the mangrove rehabilitation program increased after the activity.